Corrugated Shell Displacements During the Passage of a Vehicle Along a Soil-Steel Structure - Machelski Czesław; Mumot Marcin (Studia Geotechnica et Mechanica, 2016)
Corrugated steel plates are highly rigid and as the constructions can be immersed in soil, they can be used as soil-steel structures. With an increase of cover depth, the effectiveness of operating loads decreases. A substantial reduction of the impacts of vehicles takes place as a road or rail surface with its substructure is crucial. The scope of load’s impact greatly exceeds the span L of a shell. This article presents the analysis of deformations of the upper part of a shell caused by a live load. One of the assumptions used in calculations performed in Plaxis software was the circle-shaped shell and the circumferential segment of the building structure in the 2D model. The influence lines of the components of vertical and horizontal displacements of points located at the highest place on the shell were used as a basis of analysis. These results are helpful in assessing the results of measurements carried out for the railway structure during the passage of two locomotives along the track. This type of load is characterized by a steady pressure onto wheels with a regular wheel base. The results of measurements confirmed the regularity of displacement changes during the passage of this load.